2021
DOI: 10.1177/09763996211030884
|View full text |Cite
|
Sign up to set email alerts
|

New Farm Acts and Emerging Market Forms: Implications for Farmers

Abstract: This article examines the implications of new farm laws enacted by the Government of India in 2020 on farming and farmers. There are divergent opinions of experts and of the Government of India and the farmers’ unions on the expected benefits/losses to farmers. This article seeks guidance from economic theory on determination of prices of inputs and outputs under different market forms. The farm laws raise concerns about their potential to alter the organizational forms of production, marketing and storage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This might enable them to inflate their agriculture income to save income tax. It can be observed that several business class people and elite-class individuals possess agricultural land or farmhouses (Gill, 2021). This tax evasion or exemption will seriously disturb the revenue of the country and impact the formulation of fiscal policies in the long run.…”
Section: Farmers Arhatiyas and The Corporate Connection: Pros And Consmentioning
confidence: 99%
“…This might enable them to inflate their agriculture income to save income tax. It can be observed that several business class people and elite-class individuals possess agricultural land or farmhouses (Gill, 2021). This tax evasion or exemption will seriously disturb the revenue of the country and impact the formulation of fiscal policies in the long run.…”
Section: Farmers Arhatiyas and The Corporate Connection: Pros And Consmentioning
confidence: 99%